1994
DOI: 10.1001/archpsyc.1994.03950090052008
|View full text |Cite
|
Sign up to set email alerts
|

Buspirone Treatment of Anxious Alcoholics

Abstract: Buspirone appears to have a useful role in the treatment of anxious alcoholics. Further research is needed to clarify which patient characteristics and concomitant treatments result in optimal response to buspirone therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(84 citation statements)
references
References 53 publications
1
78
0
5
Order By: Relevance
“…Buspirone has been studied in such patients. One study (Kranzler et al, 1994) found an advantage in terms of drinking and anxiety but an earlier study (Malcolm et al, 1992) did not.…”
Section: Anxiety and Panic Disordermentioning
confidence: 93%
“…Buspirone has been studied in such patients. One study (Kranzler et al, 1994) found an advantage in terms of drinking and anxiety but an earlier study (Malcolm et al, 1992) did not.…”
Section: Anxiety and Panic Disordermentioning
confidence: 93%
“…[7] Depreşmeyi önlemek için uygulanan programlar istek azaltıcı veya anksiyolitik ilaç-larla birlikte de kullanılabilmektedir. [50][51][52] İlaçların genellikle uzun süre ve düzenli kullanılması gerekmektedir. Ancak konu ile ilgili yapılan araştırmalarda hastaların ilaç almayı reddetme, tedaviyi yarıda bırakma, düzenli kullanım konusunda aile üyeleri ve sağlık ekibiyle işbirliği yapmama gibi tedaviye uyumsuzluk olarak tanımlanabilecek davranışlar gösterdikleri saptanmıştır.…”
Section: Depreşmeyi öNlemede Bilişsel Davranışçı Modelunclassified
“…Esta resultaría de la interacción disfuncional de mecanismos serotoninérgicos, noradrenérgicos, gabérgicos y glutaminérgicos, estando relacionado el "reinforcement" o refuerzo primario con mecanismos dopaminérgicos y endorfínicos (110) . En consonancia con este modelo se han realizado estudios con antagonistas serotoninérgicos como ritanserina (111) ; antagonistas serotoninérgicos como buspirona (112,113,114) ; inhibidores de la recaptación de serotonina como fluvoxamina, fluoxetina, citalopram, zimelidina (115) ; sustancias dopaminérgi-cas como lisuride y tiapride (116) y, actualmente, se está estudiando la efectividad de flupentixol; antagonistas opiáceos como naltrexona (117,118) ; finalmente, sustancias antiglutaminérgicas como el acamprosato (119) . Mientras que los psicofármacos clásicos parecen ser efectivos en pacientes que presentan comorbilidad psiquiátrica, los resultados clínicos de la incorporación de sustancias anti-craving resultan dispares según qué grupo de pacientes con enfermedad alcohólica sea tratado.…”
Section: Medidas Terapéuticas Y Preventivas Tras El Tratamiento De Deunclassified